Islamic Economic Concepts To Form Community Welfare From The Perspective Of Ibnu Khaldun's Thinking - Nurcahyo, Satria Avianda; Isnawati, Setya Indah; Widagdo, Teguh Harso; Rizal, Achmad (Universitas Islam Negeri (UIN) Walisongo Semarang, 2024)
Purpose - This research aims to review Ibn Khaldun's thoughts regarding social welfare, Ibn Khaldun revealed that Allah outlined economic activities as an inseparable part of the social responsibilities that exist in society, and their incompleteness could threaten the continuity of world life and human existence.Method - This research is using a type of normative research, applying a library approach and a conceptual approach.Result - The result of this research indicates Ibnu Khaldun stated that Allah established muamalah activities as an integral form of responsibility in community life. Non-fulfillment can threaten world life and human welfare. In formulating three basic reasons for engaging in economic activity, Ibnu Khaldun explains that this is not only about fulfilling personal life needs. Ibnu Khaldun believes that the price of a good or service is influenced by the dynamic interaction between demand and supply. This concept highlights the interrelated relationship between the forces of demand and supply in determining the value of a product or service. Implication - This study It is hoped that there will be management and supervision of market prices by the state in the field, as suggested by Ibn Khaldun in his great work Muqadimmah.Originality - In the economic context, Ibnu Khaldun also highlighted the importance of government vigilance regarding the amount of money in circulation.